Issues and the use of social media in reference services by academic library personnel in Nigeria (2017)
Social Media platforms have revolutionized the patterns libraries serve their clientele as well as augment reference services delivery. This study seeks to address the issues militating against the integration of social media in reference services and the level of use by academic library personnel in Nigeria. Questionnaire instrument was used for data collection. 100 copies of questionnaire were distributed to the librarians and other library personnel at the national seminar in 2015 held at Kogi State University, Nigeria. 62 copies were filled and returned, given a response rate of 62%. The study found that academic libraries’ personnel in Nigeria have embraced the regular use of social media, but their application of these media in reference services is quite low. The issues contending with the integration of social media in reference services by academic library personnel in Nigeria include lack of awareness and training on the application of social media to reference services, coupled with infrastructural and technological problems. The study advocated for awareness and training programmes on the use of social media within the academic community and provision of appropriate and adequate infrastructure in academic libraries